2006
DOI: 10.1097/01.pas.0000179117.38787.57
|View full text |Cite
|
Sign up to set email alerts
|

Polyoma Virus-Associated Cellular Changes in the Urine and Bladder Biopsy Samples

Abstract: Polyoma (BK) virus-type cellular changes are occasionally reported in urine specimens, yet rarely detected in histologic sections of bladder biopsies. A total of 762 predominantly voided urine specimens with a cytologic diagnosis of polyoma virus-type change were retrieved from the cytopathology files of the Johns Hopkins Hospital over a 15-year period (1988-2003). Biopsies were available for 33 cases (29 patients) following or preceding the urinary cytology (mean interval, 210 days). The biopsies originated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…Furthermore, a statistically significant association between urine cytological evidence of PyV infection (decoy cells) and BC was also demonstrated in immunocompetent patients (18). Despite this experimental and epidemiological evidence, clinical cases of PyV-associated urological malignancies are rare and presented mainly as isolated case reports, mostly in transplant recipients or rarely in immunocompetent patients (17,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a statistically significant association between urine cytological evidence of PyV infection (decoy cells) and BC was also demonstrated in immunocompetent patients (18). Despite this experimental and epidemiological evidence, clinical cases of PyV-associated urological malignancies are rare and presented mainly as isolated case reports, mostly in transplant recipients or rarely in immunocompetent patients (17,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of paraffin blocks of renal specimens obtained from the patients made it possible to use this method. Immunohistochemical staining with SV40 in paraffin blocks prepared before have been shown to be efficient in several studies reported so far (21,22). …”
Section: Discussionmentioning
confidence: 99%
“…52 In the studies by Fioriti et al and Monini et al, BKV sequences were found to be present at a high frequency in bladder carcinomas. 78, 79 Weinreb et al reported a significant association between urine cytology suggestive of PyV infection and subsequent diagnosis of bladder carcinoma. 75 Alexiev et al reported two cases of kidney transplant patients who developed PVAN and unspecified BKV infection followed by the development of carcinoma of the urinary bladder several years post transplantation.…”
Section: Bkv and Human Tumorsmentioning
confidence: 99%
“…79 concluded that there is evidence for a significant link between BKV expression and prostate cancer development, particularly between BKV infection and cancer risk ( Table 2). 98 …”
Section: Bkv and Human Tumorsmentioning
confidence: 99%
See 1 more Smart Citation